Jerusalem Municipal Council 1930-1945 (Filastin newspaper as a source)‎ - Alshora, Salih Ali (Dirasat: Human and Social Sciences, 2025)
Objectives: This study highlights the role of Filastin newspaper in covering the Jerusalem Municipal Council, focusing on the internal conflicts within the council. Methods: The study used historical research methods, tracking the newspaper’s reports on the council within the context of the evolving and accelerating historical events. Results: The findings show that Filastin emphasized the Arab stance on managing Jerusalem’s municipal affairs, opposing British and Jewish attempts to alter the city’s demographic reality. Conclusions: The study aimed to shed light on how Filastin addressed the Jerusalem Municipal Council and its key positions from 1930 to 1945. It influenced locals to participate in elections to prevent these roles from shifting to Jewish hands and explored the newspaper’s role in siding with different factions, both between Arabs and Jews and among Arabs themselves. It also examined the political leanings of the newspaper as reflected in its coverage of the council’s affairs.